Using Repeated Cross-Sections to Explore Movements in and out of Poverty - Dang, Hai-Anh; Lanjouw, Peter; Luoto, Jill; McKenzie, David (2012)
Movements in and out of poverty are of core interest to both policymakers and economists. Yet the panel data needed to analyze such movements are rare. In this paper, the authors build on the methodology used to construct poverty maps to show how repeated cross-sections of household survey data can allow inferences to be made about movements in and out of poverty. They illustrate that the method permits the estimation of bounds on mobility, and provide non-parametric and parametric approaches to obtaining these bounds. They test how well the method works on data sets for Vietnam and Indonesia where we are able to compare our method to true panel estimates. The results are sufficiently encouraging to offer the prospect of some limited, basic, insights into mobility and poverty duration in settings where historically it was judged that the data necessary for such analysis were unavailable.